DAKWAH YANG BERLITERASI MEDIA: UPAYA DERADIKALISASI DI LINGKUP KAMPUS IAIN KENDARI - Arnus, Sri Hadijah (Palita: Journal of Social Religion Research, 2017)
The new media era is a time when every individual has a virtual community other than their community in the real world. The high interactivity of social media and its decentralized nature allows for the enormous flow of information that inflicts social media users. This of course can have a positive impact, but it can also bring a negative effect. To counteract the negative effects of social media, media literacy is needed, in this case for students. Media literacy is done to form a filter on students, in the face of negative exposure in social media that can give effect to the formation of a stereotype of a person against a particular ethnic or religious groups, as well as information charged with radicalism. It is deemed necessary to see IAIN Kendari students who have very diverse ethnic backgrounds and different organizational backgrounds of different groups, thus affecting the difference of individuals in making decisions or in dealing with various forms of information from social media. Media literacy is done through the way of da'wah is to provide understanding to the students how the media to construct a message that is combined with messages that contain knowledge about Islam. This paper will describe the media literacy model for IAIN Kendari students with the form of da'wah which aims to counteract the understanding of radicalism obtained through social media, for IAIN students Kendari.